IMPROVING HEALTH CARE-SEEKING BEHAVIORS OF CARETAKERS OF CHILDREN AGED 0-59 MONTHS IN BUGIRI DISTRICT OF EASTERN UGANDA THROUGH THE IMPLEMENTATION OF THE INTEGRATED COMMUNITY CASE MANAGEMENT PROJECT: PRE AND POST IMPLEMENTATION EVALUATION. - MUKEMBO, ALEX; Nangosha, Elisha; Marcus, Seth; Baigereaza, Isaac Charles; Kisakye, Gloria Ndagire; Balwaniki, Chris Arnold; Opio, Chris Derrick; Musasizi , Benon; Mirembe, Kalumba Mirembe; Nabunnya , Victoria; Naula Ofwono, Rose; Nantenza, Joan; et al. (Student's Journal of Health Research Africa, 2024)
Introduction Malaria, diarrhea, and pneumonia are the leading causes of death among children under five in Uganda and similar countries. The Integrated Community Case Management (iCCM) strategy aims to improve access to and use of services for these conditions at the community level. World Vision Uganda and Bugiri District, with funding from the Pfizer Foundation, implemented an 18-month iCCM project in Bugiri district. This article assesses the project's impact on health-seeking behaviors among caregivers of children aged 0-59 months for these conditions. Methodology 453 Village Health Teams (VHTs) received a 7-day training on basic VHT skills and Integrated Community Case Management (ICCM). They were equipped with ICCM drugs, sick child job aids, and thermometers. VHTs conducted home visits to educate caretakers, and test, and treat sick children for three conditions. Severe cases were referred to health facilities. They received quarterly mentorships and used HMIS 097B to report data quarterly. Anonymized patient data were analyzed monthly using interrupted time series Poisson regression to assess intervention impact on under-five cases and mortalities. Results The number of under-five malaria cases tested and treated by VHTs significantly increased from 2209 to 12549 cases. at the same time, the number of cases managed at the health facilities increased from18040 to 35257 cases (P 0.000 CI 1.48-2.57). Under-five mortality due to malaria significantly reduced from 26 to 6 cases per 100000 (P 0.058 CI 0.95-12.8). Seeking treatment within 24 hours of the onset of signs (P=0.00), caregiver’s ability to recognize severe condition (P =0.00), and referral of severe cases to health facilities (P=0.001) improved. Conclusion Implementing iCCM significantly enhances health-seeking behaviors among caregivers of children aged 0-59 months. Recommendations Authors recommend extending iCCM programs to more districts and communities across Uganda and similar regions to ensure broader access to essential healthcare services for children under five.